Decriminalising public drunkenness: Accountability and monitoring needed in the ongoing and evolving management of public intoxication. (24th September 2020) - Pennay, Amy; Savic, Michael; Seear, Kate; Volpe, Isabelle; Manning, Victoria; Room, Robin
Abstract: In light of the recent announcement from the Victorian (Australia) state government that they are moving to decriminalise public drunkenness and replace it with a 'health‐based response', it is timely to reflect on a number of important considerations identified from the academic literature on this topic. We briefly review a number of models of health‐care delivery that have been utilised in other jurisdictions, and suggest there are opportunities at a more principled level to respond more adequately to the decriminalisation of public drunkenness in Victoria (and elsewhere). First, embedding research and evaluation, particularly that draws on the needs, views and experiences of those who are deemed to be drunk in public, is essential from the outset, and must be ongoing to enable the continual refinement of models of care. Second, significant funding and intersectoral support are needed to ensure that the laws are not tokenistic and do not remain the responsibility of police. Third, there are opportunities to put policies and principles in place to ensure that police do not use more coercive powers to address concerns around public drunkenness. Most importantly, state‐wide education and training efforts are needed alongside the repeal of the law to ensure that emergency services and health‐care workers (as well as the community), have a good understanding of the contexts and needs of people who are considered drunk in public, and consequently treat them with care and respect.